2021
DOI: 10.1002/prca.202100072
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib is significantly beneficial for de novo pediatric AML patients with low phosphorylation of the NF‐κB subunit RelA

Abstract: Purpose: The addition of the proteasome inhibitor (PI) bortezomib to standard chemotherapy (ADE: cytarabine [Ara-C], daunorubicin, and etoposide) did not improve overall outcome of pediatric AML patients in the Children's Oncology Group AAML1031 phase 3 randomized clinical trial (AAML1031) . Bortezomib prevents protein degradation, including RelA via the intracellular NF-kB pathway. In this study, we hypothesized that subgroups of pediatric AML patients benefitting from standard therapy plus bortezomib (ADEB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This secondary activation is particularly decisive also in AML, where NFκB drives clonogenicity and drug resistance, regardless of whether the downstream pathway is KMT2A-lysine methyltransferase 2A (MLL)-dependent or homeobox (HOXA)-dependent [63]. Downstream activation of NFκB in patients' AML cells abolishes response to inhibitors of upstream activating pathways, rendering patients unresponsive [64].…”
Section: Aml Stem Cells (Lsc) and Their Supporting Networkmentioning
confidence: 99%
“…This secondary activation is particularly decisive also in AML, where NFκB drives clonogenicity and drug resistance, regardless of whether the downstream pathway is KMT2A-lysine methyltransferase 2A (MLL)-dependent or homeobox (HOXA)-dependent [63]. Downstream activation of NFκB in patients' AML cells abolishes response to inhibitors of upstream activating pathways, rendering patients unresponsive [64].…”
Section: Aml Stem Cells (Lsc) and Their Supporting Networkmentioning
confidence: 99%
“…About 40% of AML patients exhibited increased activity of NF-κB by dysregulation of upstream regulators in its pathway 16 , and the primary AML cells from 35% of AML patients highly expressed NF-κB receptor agonist genes, which correlated with reduced overall survival 17 . It was further found that NF-κB signaling induced the release of cytokines that act as growth and survival factors for leukemic cells and mediated resistance of AML cells to cytarabine treatment 18 . De novo pediatric AML patients with low levels of phosphorylation of the NF-κB subunit RelA were able to benefit from standard chemotherapy containing cytarabine in combination with the proteasome inhibitor bortezomib 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of normal function of the bone marrow niche is conducive to and ultimately exacerbates the aberrant production of cytokines that are essential in mediating the control of the inflammation–regeneration cascades; yet, in leukemia, they provide protection to malignant cells. Characteristically, AML stem cells (leukemia-initiating cells) show increased activity of the inflammatory transcription factor NFκB in contrast to that of normal hematopoietic stem cells [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%